Aged leaves effect on essential components in green and oolong tea - Rahman, MM; Kalam, MA; Salam, MA; Rana, MR (International Journal of Agricultural Research, Innovation and Technology, 2014)
Tea leaf encompasses essential components like caffeine, polyphenol, lipid etc. The study was conducted to find out the essential constituents in green and oolong tea from aged tea leaves during the year of 2012. Tea leaves with different plucked aged were collected from Lackatoorah Tea Estate at sylhet district in Bangladesh. Collected leaves were processesed to make desirable samples for biochemical analysis in the laboratory of Department of Food Enginnering and Tea Technology, SUST. Results revealed that the essential constituents like moisture, caffeine, polyphenol, lipid, protein, ash, ascorbic acid, acidity and pH value in green tea made from different aged leaves were found slightly higher than oolong tea, ranged from 6.38±1.06 to 3.49±0.59%; 4.91±0.82 to 1.49±0.24%; 30.88±5.15 to 18.23±3.04%; 7.50±1.25 to 9.58±1.59%; 13.15±2.19 to 17.33±2.88%; 3.87±1.65 to 7.86±1.31%; 48.4±8.05 to 21.3±3.55(mg); 2.13±0.68 to 1.18±0.19% and 5.52±0.11 to 5.97±0.18%, respectively. Similarly, the moisture, caffeine, polyphenol, lipid, protein, ash, ascorbic acid, acidity and pH value from different aged leaves were found in oolong tea from 6.19±1.04 to 2.98±0.49%; 4.68±0.78 to 1.11±0.19%; 20.89±3.48 to 8.23±1.37%; 6.40±1.07 to 9.13±1.52%; 13.03±2.17 to 17.19±2.86%; 3.44±0.58 to 7.57±1.27% 6.44±1.08 to 0.98±0.17 (mg); 2.02±0.34to 1.02±0.17% and 5.53±0.11 to 5.97±0.20%, respectively. Therefore, young tea leaves (i.e. 5 to 8 days tea leaves) should be plucked for considering useful constituents in processed green tea and oolong tea. DOI: http://dx.doi.org/10.3329/ijarit.v3i2.17845 Int. J. Agril. Res. Innov. & Tech. 3 (2): 54-58, December, 2013